Role of reservoir regulation and groundwater feedback in a simulated ground‐soil‐vegetation continuum: A long‐term regional scale analysis. Issue 8 (23rd August 2021) - Wei, Jianhui; Dong, Ningpeng; Fersch, Benjamin; Arnault, Joël; Wagner, Sven; Laux, Patrick; Zhang, Zhenyu; Yang, Qianya; Yang, Chuanguo; Shang, Shasha; Gao, Lu; Yu, Zhongbo; et al.
Abstract: The regional terrestrial water cycle is strongly altered by human activities. Among them, reservoir regulation is a way to spatially and temporally allocate water resources in a basin for multi‐purposes. However, it is still not sufficiently understood how reservoir regulation modifies the regional terrestrial‐ and subsequently, the atmospheric water cycle. To address this question, the representation of reservoir regulation into the terrestrial component of fully coupled regional Earth system models is required. In this study, an existing process‐based reservoir network module is implemented into NOAH‐HMS, that is, the terrestrial component of an atmospheric–hydrologic modelling system, namely, the WRF‐HMS. It allows to quantitatively differentiate role of reservoir regulation and of groundwater feedback in a simulated ground‐soil‐vegetation continuum. Our study focuses on the Poyang Lake basin, where the largest freshwater lake of China and reservoirs of different sizes are located. As compared to streamflow observations, the newly extended NOAH‐HMS slightly improves the streamflow and streamflow duration curves simulation for the Poyang Lake basin for the period 1979–1986. The inclusion of reservoir regulation leads to major changes in the simulated groundwater recharges and evaporation from reservoirs at local scale, but has minor effects on the simulated soil moisture and surface runoff at basin scale. The performed groundwater feedback sensitivity analysis shows that the strength of the groundwater feedback is not altered by the consideration of reservoir regulation. Furthermore, both reservoir regulation and groundwater feedback modify the partitioning of the simulated evapotranspiration, thus affecting the atmospheric water cycle in the Poyang Lake region. This finding motivates future research with our extended fully coupled atmospheric–hydrologic modelling system by the community. Abstract : An existing process‐based reservoir network module is implemented into the terrestrial component NOAH‐HMS of the atmospheric–hydrologic modelling system WRF‐HMS. The inclusion of reservoir regulation leads to major changes in the simulated groundwater recharges and evaporation from reservoirs at local scale, but does not alter the strength of the groundwater feedback. Reservoir regulation and groundwater feedback play different roles in modifying the regional terrestrial water cycle for the Poyang Lake basin, particularly with respect to the partitioning of the simulated evapotranspiration.